2010
DOI: 10.1111/j.1365-2605.2010.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dendritic cells in testicular draining lymph nodes in a rat model of experimental autoimmune orchitis

Abstract: The maturation state of dendritic cells (DC) is regarded as a control point for the induction of peripheral tolerance or autoimmunity. Experimental autoimmune orchitis (EAO) serves as a model to investigate inflammatory-based testicular impairment, which ranks as a significant cause of male infertility. This work aimed to determine whether DC enrichment occurs organotypically in testicular draining lymph nodes (TLN) compared with LN draining the site of immunization (ILN) and thus contributes to the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
2
25
0
1
Order By: Relevance
“…In this line, our previous results showing a significant increase in IL12p35 mRNA expression by the dendritic cells from rats with focal EAO (Guazzone et al 2011) provide evidence in support of a Th1 response.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this line, our previous results showing a significant increase in IL12p35 mRNA expression by the dendritic cells from rats with focal EAO (Guazzone et al 2011) provide evidence in support of a Th1 response.…”
Section: Discussionsupporting
confidence: 75%
“…The fact that none of the Teff cell subsets detected in EAO testis showed evidence of significant production of IL4 may be due to the inhibitory effect of Th1 cytokines on proliferation and cytokine production by Th2 cells (Gajewski & Fitch 1988). Although Teff cells did not express IL10, our previous results showing IL10 mRNA expression in testicular and lymph node dendritic cells of EAO but not N and C rats demonstrate that this cytokine is overexpressed under inflammatory conditions (Rival et al 2007, Guazzone et al 2011.…”
Section: Discussionmentioning
confidence: 55%
“…In rat EAO, DCs exhibit mature properties. 46 Lymphocytes are always found in the interstitial spaces of the rat testis under physiological conditions. 47 Most testicular lymphocytes are T cells, with CD8 1 cells being more predominant and CD4 1 cells more rare.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…5,6,30 TH+CFA+BP-induced EAO mice sera immunologically or immunohistochemically react with germ cells behind the BTB (=spermatids and spermatocytes) and also against testicular components outside the BTB (=spermatogonia, Sertoli cells, Leydig cells and the basement membrane of the seminiferous tubules). 5,30 In contrast, TGC-induced EAO is unique in that serum autoantibodies are only against sperm and spermatids. In the present study, we found that there are some molecular differences between TGC and ES antigens that react with autoantibodies.…”
Section: Discussionmentioning
confidence: 96%
“…1,2,4 It was also revealed that macrophages, professionally antigen-presenting dendritic cells, and putative function of mast cells play an important role in development of EAO. 5,6 Classically, the immunization of mice with a testicular homogenate (TH) emulsified in complete Freund's adjuvant (CFA) followed by the intravenous injection of Bordetella pertussis (BP) is necessary for the induction of EAO, in which inflammatory cell responses are evoked in the testes, epididymis, and vas deferens. 7,8 Enzyme-linked immunosorbent assay (ELISA) analyses of the sera of TH+CFA+BP-induced EAO mice revealed that the titer of autoantibodies against epididymal spermatozoa (ES) increases compared with that in controls and that the titer of IgG is significantly higher than that of IgA or IgM.…”
Section: Introductionmentioning
confidence: 99%